Edukasi Pemanfaatan Buku Saku Menu Makanan Sehat Sebagai Gerakan Pencegahan Stunting di Desa Nangsri Manisrenggo Klaten - Zesika Intan Navelia; Fatya Nurul H Fatya Nurul H; Dian Monalisa R; Novita Puspita D (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
Background: Stunting is a condition in which infants or children under five years old are malnourished during pregnancy and after birth. By the time a child is two years old, stunting may be present. Sustained malnutrition can cause children to be shorter or stunted than children of the same age. The purpose of the community service activity is to teach mothers who have stunted toddlers to utilize a healthy food menu pocket book. Methods: In Nangsri Manisrenggo Village, Klaten, this community service was carried out through counseling and practice of utilizing a healthy food menu pocket book with a total of 20 participants. Community service participants are mothers who have stunted toddlers. Results: Community service on the utilization of healthy food menu pocket books for toddlers in preventing stunting has proven effective. The speaker made the participants very enthusiastic about what they learned. Conclusion: The pretest and posttest results of mothers' knowledge about the use of a balanced menu pocket book increased to 75%, increasing awareness of the importance of paying attention to nutritional fulfillment for stunting toddlers.